2009
DOI: 10.1016/j.fertnstert.2008.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of polycystic ovary syndrome on cardiovascular risk

Abstract: 2 CAPSULEPostmenopausal women with PCOS have increased cerebro-vascular events and cardiovascular morbidity. Our best long-term strategy is information, acknowledging women with PCOS of their risk for metabolic and cardiovascular diseases. 3 ABSTRACTMost available data suggest that the prevalence of cardiovascular diseases in women with polycystic ovary syndrome (PCOS) is smaller than what expected on the basis of the risk calculation during fertile age; therefore, we need many more studies on their long term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 59 publications
(43 reference statements)
0
28
0
2
Order By: Relevance
“…A high incidence of insulin resistance (IR) and cardiovascular risk factors such as hypertension, obesity, dyslipidemia and type 2 diabetes are reported in PCOS subjects [2,3], all of which increases the probability of future cardiovascular disease. In addition, several studies have indicated that PCOS subjects can develop subclinical atherosclerosis at a young age [4e6], while others have reported increased cardiovascular morbidity in these patients, though the available data are inconclusive and scarce [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A high incidence of insulin resistance (IR) and cardiovascular risk factors such as hypertension, obesity, dyslipidemia and type 2 diabetes are reported in PCOS subjects [2,3], all of which increases the probability of future cardiovascular disease. In addition, several studies have indicated that PCOS subjects can develop subclinical atherosclerosis at a young age [4e6], while others have reported increased cardiovascular morbidity in these patients, though the available data are inconclusive and scarce [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Their conclusions are still contradictory. For example, in Rizzo et al review [25], five studies concluded that PCOS women are at risk for cardiovascular diseases, which was not proved in three other studies. Definition of PCOS, cardiovascular endpoints and median age of patients were different in each study.…”
Section: Cardiovascular Pathologymentioning
confidence: 91%
“…One study reported that, after adjusting for confounders, women with polycystic appearing ovaries were more likely to have stenotic CAD (i.e., more coronary artery segments with >50 % diameter loss) than women with normal appearing ovaries ( n = 142) [ 26 ]. Eight additional studies were included in a systematic review, fi ve of which found an increased risk associated with cardiovascular endpoints in the PCOS population, while three studies found no difference in cardiac events compared to age-matched women [ 27 ]. A prospective study followed 31 of 35 women with PCOS (diagnosed in 1987 via histology at wedge resection, and confi rmed by Rotterdam criteria in 2008) and 160 age-matched controls into late menopause.…”
Section: Risk Of Fatal or Nonfatal Cardiovascular Eventsmentioning
confidence: 99%